Seismic retrofit of RC beam-column joints using the MF-EBR strengthening technique - Coelho, Mário Rui Freitas (2012)
The strengthening technique based on the use of multi-directional laminates of CFRP simultaneously glued and fixed with anchors (MF-EBR) has been recently purposed. An experimental program composed of pullout tests was carried out in order to study the bond behavior between concrete and MF-EBR system. The diameter and number of anchors, the pre-stress level applied to the anchors, and the strengthening procedures were the main analyzed parameters. The present work describes the carried-out tests and presents and analyzes the most significant obtained results.